QUANTUM DESCRIPTION OF UNSTABLE BEHAVIOR OF INTRACAVITY THIRD HARMONIC GENERATION PROCESS - S. T. Gevorgyan; M. S. Gevorgyan
In the following paper we study the quantum dynamics of the number of photons of the interacting modes, the dynamics of the quantum entropy, as well as the Wigner function of the states of the fundamental and the third harmonic modes for the process of intracavity third harmonic generation. It is shown that the quantum dynamics of the system strongly depends on the external resonant perturbation of the fundamental mode and on the coupling coefficient of the interacting modes. In the region of long interaction times, the modes of the field can be both in stable and in unstable states – depending on the above mentioned quantities. In the paper we also investigate the dynamics of transition of the system from stable to unstable state. It is shown that the third harmonic mode can localize in different unstable states with strongly different Wigner functions depending on the coupling coefficient.
Keywords: Physics; Quantum mechanics, field theories, and special relativity